Cockroach-allergen study: Allergen patterns of three common cockroach species probed by allergic sera collected in two cities - Kang, Bann C.; Wilson, Marijo; Price, K.H.; Kambara, T. (Journal of allergy and clinical immunology, 1991)
Antigens/allergens of three common cockroach extracts, crude whole body extract of the American cockroach (CRa-A), crude whole body extract of the German cockroach (CRa-G), and crude whole body extract of the Oriental cockroach (CRa-O), were studied with crossed immunoelectrophoresis, crossed radioimmunoelectrophoresis, and Western blot analysis. Sera of cockroach-allergic patients with asthma, 10 from Chicago, Ill. (C group) and six patients from Lexington, Ky. (L group), were used; results were then compared with sera of control subjects with asthma. Qualitative differences in protein bands were noted among CRa-A, CRa-G, and CRa-O by crossed immunoelectrophoresis and sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Allergen bands on Western blot were analyzed for distribution by molecular weight (MW) with relative intensity scores. Results were compared by species and by geography. Two to 12 allergenic bands of variable MW (14 kd to >116 kd) were identified by 13 of 16 individual sera from cockroach-allergic patients from all three extracts. CRa-A demonstrated 55 bands with an intensity score of 125; CRa-G, 58 bands with an intensity score of 100; and CRa-O, 51 bands with an intensity score of 108. Allergenic bands of CRa-A were identified by six sera of the C group and one sera of the L group, whereas bands of both CRa-G and CRa-O were noted by nine sera of the C group and four sera of the L group. All three species had an allergen band in MW range of 40 to 45 kd that reacted to most sera from cockroach-allergic patients with asthma.